Energy Efficiency Analysis of the Implementation of On-Grid Solar Power System at Pertamina Labuhan Deli Fuel Depot - Enos Anggiat Simanjuntak; Parlin Siagian; Zulkarnain Zulkarnain (Publikasi Indonesia, 2024)
Economic growth and the increasing demand for electrical energy require a breakthrough in the provision of electrical energy, one of which is the use of renewable and environmentally friendly energy. Solar energy is one of the renewable energies that can be used as a solar PV system. This solar PV system can also be combined with the PLN network (grid) and generators to meet electrical energy needs. This study aims to find out the amount of electrical energy efficiency value that can be produced by the plant every month, and whether it can affect the electricity bill paid by PT Pertamina Patra Niaga every month. Methods This research uses observation methods and collects various data related to the installation of Solar Power Plants on the Grid starting from April to September 2024. This research contains the results of the total electrical energy produced by the solar power plant, the efficiency of the solar power plant as well as the saving costs generated after the installation of the solar power plant at the Pertamina Labuhan Deli Fuel Depot.